Processing Corn Cobs Waste as Bio Briquettes - Nugrahaeni, Dela A.I.; Anggraini, Dinar P.; Firmansyah, Arif (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
Corn cobs waste can be processed into bio briquettes, where it can be used asalternative fuels to replace fossil fuels. Making of bio briquettes are easy, low cost,simple technology and friendly to environment. The purpose of making journal biobriquettes are to review characteristics corn cobs waste to get optimal processconditions and analyze calorific value was produced from corn cobs waste. Corn cobs waste is chosen as raw material for making bio briquettes because produce high waste and less utilized optimally. Therefore, corn cobs waste is processed into bio briquettes so can increase economy value. Making of Bio briquettes are expected can be applied in domestic industry and industry developing to fulfill energy needs.